Interactions of HIV protease inhibitors with ATP-dependent drug export proteins - Gutmann, Heike; Fricker, Gert (Molecular pharmacology, 1999)
We used renal proximal tubules from a teleost fish (killifish;Fundulus heteroclitus), fluorescent substrates and confocal microscopy to study the interactions between human immunodeficiency virus protease inhibitors and drug-transporting ATPases. Both saquinavir and ritonavir inhibited luminal accumulation of a fluorescent cyclosporin A derivative (a substrate for P-glycoprotein) and of fluorescein methotrexate [a substrate for multidrug resistance-associated protein 2 (Mrp2)]. Of the two protease inhibitors, ritonavir was the more potent inhibitor of transport by a factor of at least 20. Ritonavir was at least as good an inhibitor of P-glycoprotein- and Mrp2-mediated transport as cyclosporin A and leukotriene C4, respectively. Inhibition of P-glycoprotein- and Mrp2-mediated transport was not due to toxicity or impaired metabolism, because neither saquinavir nor ritonavir inhibited transport of fluorescein on the renal organic anion system. Experiments with a fluorescent saquinavir derivative showed strong secretion into the tubular lumen that was inhibited by verapamil, leukotriene C4, saquinavir, and ritonavir. Together, the data demonstrate that saquinavir, and especially ritonavir, are potent inhibitors of P-glycoprotein- and Mrp2-mediated transport. The experiments with the fluorescent saquinavir derivative suggest that these protease inhibitors may also be substrates for both P-glycoprotein and Mrp2.
Gesehen am 26.04.2017